PEMBIAYAAN GRIYA BANK SYARI’AH MANDIRI (STUDI KASUS BANK SYARI’AH MANDIRI CABANG KENDARI) - Muhamad Turmudi (Institut Agama Islam Negeri Kendari, 2015)
AbstractAs the financial institutions, Syariah Mandiri’s bank provides an offer a house financing program which consist of house financing BSM, house subsidy BSM, house BSM Optimal. Those program is a financing programto purchase or renovate the house, healthy simple house (RSH), house-shop, etc. either for new or second place in the developer and non-developer environment. Starting on May 20, 2013 the branch of Mandiri Syariah’s Kendari has channeled financing housing approximatelyRp.78.308.993.645,77 with the number of customers 234 people thatdedicated to financing houses, house-shop and residential undertaken by the developer. The contract used in transaction program that bank is skim ba’i al-murabahah, where the purchase contract between the bank and thecustomer. In this program, bank buys items needed and sell the customer by same cost plus the margin profit that has been agreed both.Keywords: Mandiri Syariah’s bank, Housing Financing, the Contract of Murabahah AbstrakBank Syari’ah Mandiri sebagai lembaga keuangan memberikan suatupenawaran pembiayaan pemilikan rumah dengan menerbitkan program Pembiayaan Griya BSM, Griya BSM Bersubsidi serta Griya BSM Optima.Program ini merupakan program pembiayaan untuk pembelian ataupunmerenovasi rumah tinggal, rumah sederhana sehat (RSH), ruko dan lainsebagainya baik baru maupun bekas di lingkungan developer maupun non developer. Per tanggal 20 Mei 2013 Bank Syari’ah Mandiri Cabang Kendari dalam perannya telah menyalurkan pembiayaan pemilikan rumah sebesar Rp.78.308.993.645,77 dengan jumlah nasabah 234 orang yang diperuntukkan bagi pembiayaan rumah tinggal, ruko serta perumahan yang dikerjakan oleh pengembang. Akad yang digunakan pada transaksi program pembiayaan kepemilikan rumah di Bank Syari’ah Mandiri Cabang Kendari adalah skim ba’i al-murabahah yaitu akad jual beli antara bank dan nasabah, dimana bank membeli barang yang dibutuhkan dan menjualnya kepada nasabah sebesar harga pokok ditambah dengan keuntungan margin yang disepakati. Kata kunci: Bank Syari’ah Mandiri, Pembiayaan Kepemilikan Rumah, Akad Murabahah.